2021
DOI: 10.1111/wrr.12970
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation and associations of leg ulcers in adult sickle cell patients

Abstract: Sickle leg ulcer (SLU) occurs as a result chronic occlusion of the vasculature with consequent necrosis of the skin and subcutaneous tissue usually in proximity of the malleoli. The description of clinical associations and the simultaneous occurrence of SLU and other complications of SCD compared to the non‐SLU patients was the aim of this work. A total of 272 (60.8% males and 39.2% females) patients were captured during this time period out of which 68 (51 males and 17 females) had SLU out of whom 20 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Many studies have shown an association between leg ulcers and echocardiographic signs of pulmonary hypertension. 13,19,68,69 Parent et al confirmed these results using right heart catheterization, 70 the gold standard for pulmonary hypertension diagnosis. These observations support systematic screening of pulmonary hypertension in SCD patients with leg ulcers.…”
Section: Haemolysismentioning
confidence: 88%
See 4 more Smart Citations
“…Many studies have shown an association between leg ulcers and echocardiographic signs of pulmonary hypertension. 13,19,68,69 Parent et al confirmed these results using right heart catheterization, 70 the gold standard for pulmonary hypertension diagnosis. These observations support systematic screening of pulmonary hypertension in SCD patients with leg ulcers.…”
Section: Haemolysismentioning
confidence: 88%
“…Several studies reported a high incidence of leg ulcers in males compared to females with SCD. 11,13,[15][16][17][18] The male to female ratio was approximately 2 in the United States and Nigeria. 16,17 In contrast, other studies reported a similar incidence between males and females.…”
Section: General Conditionsmentioning
confidence: 99%
See 3 more Smart Citations